Improvement of Voltage Stability Index Of Radial Distribution Networks - Gupta, Namita (EIED, 2017)
Active and reactive power losses are a major challenge in the field of power system. Many techniques have been evolved for reducing these losses and hence improving voltage profile. Power compensation has become very important so as to improve power system stability and hence preventing the operation of system closer to the voltage stability boundaries. Reactive power compensation plays a vital role in improving the voltage profile and planning of power system. This dissertation represents Dragonfly Algorithm approach to minimize power losses and improve voltage stability index of system by optimal placement of capacitors in radial distribution networks. Firstly, load flow has been performed to determine the actual losses and voltages at different nodes of system without compensation called the base case. Next the optimal location and size of the capacitor to be installed has been found. Location has been determined by calculating the Loss Sensitivity Factor at each node. For size determination, Dragonfly optimization algorithm has been used. After installing capacitors at the candidate nodes, again the load flow had been performed to justify the objective. The suggested system is tried out on standard 33 node and 85 node radial distribution networks and results have been compared with other existing methods. The proposed Dragonfly Algorithm has been implemented to outperform the existing popular and powerful algorithms.
M.E. Thesis
Keywords: Voltage Stability Index; Radial Distribution Network; Loss sensitivity factor; Dragonfly Algorithm